Rebeldes com causa: narrativa construída na formação colaborativa de professores na escola - Speakes, Neusely Fernandes Silva (2017)
This research visited the collaborative continuing professional education program for in-service teachers at the Municipal Elementary School José Áureo Monjardim, part of the municipal school system in the city of Vitória, Espírito Santo. The program was a place of reflection. The research analyzed the school’s actions as well as its relationship with the official agenda maintained by the city of Vitória-ES. The objective of this work was to outline some of the collective actions taken by teachers in the search for continuity in professional education and the results on individual learning, the strengthening of the group, and pedagogical practice with students. The research also investigated how a group strengthened by continuing education responds to situations of conflict, oftentimes proposed by education officials. Theoretical foundations were provided by authors such as John Dewey, Andy Hargreaves, Jose Contreras, Kenneth Zeichner and Henry Giroux, among others who helped to understand the process of preparing teachers who are concerned with their own reality, that of the group, and of their school, as well as how to act upon that reality. Theoretical support especially contributed to highlighting the concept of education, autonomy, collegiality, reflection and resistance which were benchmarks for comprehending the teachers’ actions and the collaborative professional education at the school. Data collection was carried out using dialogical encounters with a group of 05 teachers from the school. During the encounters, the teachers shared experiences which differed from those practiced in other schools within the municipal school system in that their program presented an accentuated appreciation for collective study. The group meets every week for two hours to study specific, predetermined topics. The thematic choice is usually made in an attempt to answer the questions that arise in everyday school life. The research investigated how, on the basis in their reflections, the group made decisions and adopted particular stances that changed the pedagogical organization of the school and, at times, resisted government determinations that it considered to be contrary to that which was desired and planned by the group. The school has a history of standing up to and opposing the Municipal Secretary of Education, which is why the Secretary tried to prevent the existence of the study group. To understand this school and its collective study group as a space for reflection, capable of creating and strengthening autonomy, as well as the spirit to resist anything that does not favor the school, this research was inspired by the methodological work of Ivor Goodson and Scherto Gill who use narrative and discussion as pedagogy practice. Narrative pedagogy brings forth the voice of the agents and allows them to assume the role of protagonist. Included in the data analyzed were teachers' statements and school documents. The results reveal that from the dialogues / narrative emerge the memories of an individual and collective time lived and shared that resulted in changes in behavior and understanding in the individuals / collective subject about the reality surrounding them, about themselves, and their personal and professional intentions and meanings. They reveal a process of collaborative reflection, which becomes self-knowledge and learning about the profession, that is, continuing education: on the one hand, a stockpile of learning, knowledge and skills, shared and used by the group to question the events of everyday life and, on the other hand, a "narrative identity", a learning strategy for adults who share knowledge, situations, times and professional spaces